2012
DOI: 10.1136/bjophthalmol-2012-302434
|View full text |Cite
|
Sign up to set email alerts
|

Macular ultrastructural features in amblyopia using high-definition optical coherence tomography

Abstract: Using enhanced high-definition SD-OCT, amblyopic eyes demonstrated qualitative and quantitative differences in macular features, possibly representing signs of immaturity compared with normal fellow eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 20 publications
3
46
2
1
Order By: Relevance
“…Perhaps the number of patients we included was insufficient to evaluate the aforementioned factors. Recent OCT studies have demonstrated the presence or absence of a foveal bulge at the central fovea is significantly associated with VA in eyes with albinism, 23 occult macular dystrophy, 24 amblyopia, 25 branch retinal vein occlusion, 26 and RRD. 27 Centripetal migration of cone cells and thinning of individual foveal cone OS reportedly results in an increase in foveal cone OS density.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps the number of patients we included was insufficient to evaluate the aforementioned factors. Recent OCT studies have demonstrated the presence or absence of a foveal bulge at the central fovea is significantly associated with VA in eyes with albinism, 23 occult macular dystrophy, 24 amblyopia, 25 branch retinal vein occlusion, 26 and RRD. 27 Centripetal migration of cone cells and thinning of individual foveal cone OS reportedly results in an increase in foveal cone OS density.…”
Section: Discussionmentioning
confidence: 99%
“…Recent OCT studies have shown that the presence or absence of a foveal bulge at the central fovea is significantly correlated with VA in eyes with albinism, 23 occult macular dystrophy, 24 amblyopia, 25 and branch retinal vein occlusion. 26 Hasegawa et al 27 reported a significant correlation between the presence of foveal bulge and BCVA after successful RRD repair with vitrectomy.…”
mentioning
confidence: 99%
“…A value of 10 μm was chosen, as coefficients of repeatability for macular thickness measured by fdOCT in eyes with healthy retinas have been reported at 1.0 to 3.5 %, or up to about 9.5 μm [31,32]. Interocular differences in macular thickness of 0.0±13.4 μm as measured by fdOCT have been reported for children 6-17 years of age [21]. Using this standard deviation, we determined that a sample size of 16 in each group was sufficient.…”
Section: Sample Sizementioning
confidence: 99%
“…Eye growth during childhood is a visually guided process, and degradation or alteration of visual input may disrupt growth [18]. Numerous studies have evaluated the effects of early abnormal visual experience in relation to macular thickness in children with strabismic and anisometropic amblyopia [19][20][21][22][23][24]. Despite the obvious ocular problems, in light of the unique challenges of retinal imaging in children, there are few reports on retinal structure in children with Down syndrome.…”
Section: Introductionmentioning
confidence: 98%
“…The advantages of SD-OCT include highly increased image acquisition, approximately twice the axial resolution, relatively reduced motion artifact, and significantly increased signal-tonoise ratio as compared with TD-OCT. 8,[10][11][12][13][14][15] Accordingly, several studies on macular thickness and volume using SD-OCT have been reported recently among children, young adults, or a wide range of age with one or mixed ethnicity. 9,14,[16][17][18][19][20][21][22] However, investigation of macular thickness and its relationship with refractive error or AL in Chinese myopic children using SD-OCT have yet to be reported.…”
mentioning
confidence: 97%